Direct observation of intermediates formed during steady-state electrocatalytic O(2) reduction by iron porphyrins - Sengupta, Kushal (National Academy of Sciences, 2013)
Heme/porphyrin-based electrocatalysts (both synthetic and natural) have been known to catalyze electrochemical O(2), H(+), and CO(2) reduction for more than five decades. So far, no direct spectroscopic investigations of intermediates formed on the electrodes during these processes have been reported; and this has limited detailed understanding of the mechanism of these catalysts, which is key to their development. Rotating disk electrochemistry coupled to resonance Raman spectroscopy is reported for iron porphyrin electrocatalysts that reduce O(2) in buffered aqueous solutions. Unlike conventional single-turnover intermediate trapping experiments, these experiments probe the system while it is under steady state. A combination of oxidation and spin-state marker bands and metal ligand vibrations (identified using isotopically enriched substrates) allow in situ identification of O(2)-derived intermediates formed on the electrode surface. This approach, combining dynamic electrochemistry with resonance Raman spectroscopy, may be routinely used to investigate a plethora of metalloporphyrin complexes and heme enzymes used as electrocatalysts for small-molecule activation.